Mozart, Haydn and Early Beethoven 1781-1802 - Heartz, Daniel 1928-2019 (New York Norton, 2009)
Completing the trilogy begun with Haydn, Mozart and the Viennese School, 1740-1780 and continued in Music in European Capitals: The Galant Style, 1720-1780, Daniel Heartz concludes his extensive chronicle of the Classical Era with this much-anticipated third volume. By the early years of the nineteenth century, "Haydn, Mozart and Beethoven" had become a catchphrase?a commonplace expression signifying musical excellence. Indeed, even in his early career, Beethoven was hailed as the only musician worthy to stand beside Haydn and Mozart. In this volume, Heartz winds up the careers of Haydn and Mozart (who during the 1780s produced their most famous and greatest works) and describes Beethoven's first decade in Vienna, during which he began composing by patterning his works on the two masters. The tumult and instability of the French Revolution serves as a vivid historical backdrop for the tale. 45 illustrations; 163 music examples
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Haydn, Joseph -- 1732-1809; Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); Music history; Musical analysis; Europe